1994
DOI: 10.1109/20.334267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface stress on Barkhausen effect emissions: model predictions and comparison with X-ray diffraction studies

Abstract: A bstract-The detection of surface stress in materials is becoming increasingly important in failure analysis. In the case of ferromagnetic steels, the Barkhausen effect provides a practical tool for surface stress evaluation. However, one of the drawbacks of the method has been the lack of an underlying model theory for use in computer simulations of these effects. In recent work a model theory has been suggested and calculations of the effects of stress on the Barkhausen signal amplitude have been made. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…To assist the curve-fitting procedure (described below), the background noise was substracted from the profile in the graphs shown in the next section. As appropriate for the skin depth relationship with the excitation frequency (0.2 Hz) and the analysing frequency range (3-100 kHz), the broadband MBN signal containing multiple frequencies samples the specimen to a depth of about 0.6 mm below the surface [7].…”
Section: Article In Pressmentioning
confidence: 99%
“…To assist the curve-fitting procedure (described below), the background noise was substracted from the profile in the graphs shown in the next section. As appropriate for the skin depth relationship with the excitation frequency (0.2 Hz) and the analysing frequency range (3-100 kHz), the broadband MBN signal containing multiple frequencies samples the specimen to a depth of about 0.6 mm below the surface [7].…”
Section: Article In Pressmentioning
confidence: 99%
“…When a ferromagnetic material is subjected to an external varying magnetic field, a voltage signal is induced in a pick-up coil due to changes in magnetisation of material caused by the discrete movement of magnetic domain walls overcoming various pinning sites in the material [1]. This phenomenon of electromagnetic activity known as Magnetic Barkhausen noise [1][2][3]. Jiles and Suominen [3] while working on assessment of micro-hardness and residual stress observed that the skin-depth of MBN at the same analyzing frequency decreases for materials having higher specific electric conductivity and relative permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a strong effect of all parameters on the recorded Barkhausen noise except for the hardness which induced only slight changes of the signal [13,15]. Jiles and Suomen, showed that a varying compressive residual stress state in shot peened steel sample clearly influences the maximum Barkhausen Noise signal [19]. Kleber and Vincent also proved that residual stresses strongly affect the Barkhausen Noise signal in low carbon steel while an increasing dislocation density gives a minor contribution.…”
Section: Introductionmentioning
confidence: 91%
“…Non-destructive micromagnetic methods for the measurement of residual stress have been developed these last three decades [11][12][13][14][15][16][17][18][19][20]. The principle is based on the interaction of residual stress fields with the movement of domain walls, also called Bloch walls, and with domain rotations during the magnetization processes [11,21].…”
Section: Introductionmentioning
confidence: 99%